Creating Conversations that Lead to Learning on Poster Material - Nofrizal Nofrizal; Budiwirman Budiwirman (Postgraduate School, Universitas Negeri Padang, 2022)
Creating learning-generating conversations in poster materials for Junior High School 11 Mandau students in organizational behavior and leadership courses is a useful method for students to share their learning. Presenters share their posters with colleagues in a walking gallery format. This allows students to convey their learning experiences in an unscripted way, allowing for organic and direct conversation among class participants. Combining environmental situations with poster conversation results in more engagement between students than perhaps requiring papers alone. This activity is an interesting approach that encourages rich interaction and dialogue.